Pre-service teachers’ knowledge about classroom management from university studies and own schooling experiences—content and effects of their activation - Baier-Mosch, Franziska; Kunter, Mareike (Frontiers in Education, 2024)
We investigated two sources of classroom management knowledge in 93 pre-service teachers. The first research question focused on knowledge from university studies, which is thought to be evidence-based knowledge, and whether its use for problem solving in the classroom can be fostered by means of knowledge activation. The experiment showed that knowledge activation did not lead to higher use of knowledge from university studies and better problem solving. The second research question focused on knowledge from own schooling experiences and its content as compared to knowledge from university studies. The pre-service teachers' knowledge from own schooling was strongly focused on simple reactive strategies, only as compared to knowledge from university studies.